2014
DOI: 10.1111/ctr.12301
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of post‐traumatic psychological growth in the late years after lung transplantation

Abstract: Background Although lung transplantation improves quality of life, most psychosocial research focuses on adverse psychological and social functioning outcomes. Positive effects, particularly in the late-term years as physical morbidities increase, have received little attention. We provide the first data on a psychological benefit—posttraumatic growth (PTG)—and we focused on long-term (>5 year) survivors. Methods Among 178 patients from a prospective study of mental health during the first two years posttran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 56 publications
(95 reference statements)
3
27
0
Order By: Relevance
“…This may be associated with a sense of gratitude towards the deceased donor and the medical team, and a feeling of personal responsibility for justifying all their efforts, which may in turn mobilise a large amount of energy. 6 28 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be associated with a sense of gratitude towards the deceased donor and the medical team, and a feeling of personal responsibility for justifying all their efforts, which may in turn mobilise a large amount of energy. 6 28 …”
Section: Discussionmentioning
confidence: 99%
“…Basically post-traumatic growth can be regarded as a protective factor 12 13 that enables patients to reframe threats into challenges, thereby strengthening their psychological well-being. 14 15 Previous studies have found high levels of post-traumatic growth after lung transplantation, 6 which were even higher than those observed in patients suffering from chronic heart disease, cancer or HIV. High levels of post-traumatic growth have also been found after haematopoietic stem cell transplantation (HSCT).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The articles were Updates in Psychosomatic Medicine related to 15 subspecialties: cardiac psychiatry, [4][5][6][7][8][9] collaborative care/integrated behavioral health, 10,11 emergency psychiatry, 12,13 HIV psychiatry, [14][15][16][17][18][19][20] neuropsychiatry, 21-31 pediatric psychosomatic medicine, 32-36 psychodermatology, [37][38][39][40][41][42][43][44][45] psychonephrology, 46-55 psycho-oncology and palliative care, [56][57][58][59][60][61][62][63][64] serious mental illness, [65][66][67][68][69][70][71][72] somatic symptom disorders, 73 suicide, 74-78 transplant psychiatry, [79][80][81][82][83][84]…”
Section: Resultsmentioning
confidence: 99%